IMPLEMENTASI SISTEM INFORMASI CRM (CUSTOMER RELATIONSHIP MANAGEMENT) (Studi Pada UD. Iwek-P Adventure Kota Malang) - Muhammad Iqbal Dimasz Randy (Jurnal Administrasi Bisnis, 2014)
The purpose of this minor thesis is to describe the customer relationship management of information system, to analize the problem of customer relationship management information system, and to give an alternative solution or a new customer relationship management information system recommendation to UD. Iwek-P Adventure. Through Customer Relationship Management, companies can improve interaction with customers, not only interact directly but also at the time online, and Customer Relationship Management was present as solution to our customers can interact with each time. In addition, companies can manage information about our customers' customers and analyze customer loyalty in order to have. The method  that the writer used to write this minor thesis is a qualitative method with action research approachment. Alternative solution or recommendation Customer Relationship Management information system that was proposed by researchers through the implementation of information system with Customer Relationship Management Zurmo Customer Relationship Management that based on open source. Result of implementation of information system Customer Relationship Management is management between companies and customer relationship become easier in will be done. To enter into a relationship with customers will be more effective and efficient because it uses information system that is integrated. Keywords: Implementasi, Sistem Informasi Customer Relationship Management, CRM ABSTRAK Penelitian ini bertujuan untuk mengetahui gambaran tentang sistem informasi customer relationship managwmwnt (CRM), menganalisis permasalahan sistem informasi CRM dan memberikan alternatif solusi atau rekomendasi sistem informasi CRM yang baru pada UD. Iwek-P Adventure. Melalui CRM, perusahaan dapat meningkatkan interaksi dengan pelanggan, tidak hanya berinteraksi secara langsung tapi juga pada saat online, maka CRM hadir sebagai solusi agar pelanggan dapat berinteraksi dengan perusahaan setiap saat. Selain itu perusahaan dapat mengelola informasi tentang pelanggan dan menganalisa keinginan pelanggan demi mendapatkan kesetiaan pelanggan. Jenis penelitian yang dilakukan oleh peneliti adalah penelitian kualitatif dengan pendekatan action  research. Alternatif solusi atau rekomendasi sistem informasi CRM yang diusulkan oleh peneliti melalui implementasi sistem informasi CRM dengan Zurmo CRM yang berbasis open source. Hasil dari implementasi sistem informasi CRM adalah pengelolaan manajemen antara perusahaan dengan hubungan pelanggan menjadi lebih mudah dalam dilakukan. Menjalin hubungan dengan pelanggan akan lebih efektif dan efisien karena menggunakan sistem informasi yang terintegrasi. Kata kunci : Implementation, Customer Relationship Management Information System, CRM